A novel identity-based anonymous authentication scheme from multilinear maps. (2018) - Jing, Zhengjun; Jiang, Guoping; Gu, Chunsheng
Anonymous authentication is very useful to protect the user's privacy, and plays an important role in building e-commence where involves many partners, such as in cloud computing. With the anonymous property, ring signature provides a cryptographic tool to construct a secure authentication scheme. In this paper, we construct an identity-based ring signature (IBRS) based on Garg-Gentry-Halevi (GGH) graded encoding system which is a candidate multilinear maps from ideal lattice, and prove its security in random oracle model. Under the GGH graded decisional Diffie-Hellman (GDDH) assumption, the proposed ring signature guarantees the anonymity of signer against full keys exposure attacks. Considering unforgeability, under the GGH graded computational Diffie- Hellman (GCDH) assumption, the new scheme provides unforgeability both against selectively chosen subring attacks and insider corruption.